Structural Design Optimization and Circular Utilization Technology of Steel Hanging Plate of Bracket Bracings in Metro Tunnels Oriented by Sustainable Development - Ke Ji; Jun Zhang; Tian Su; Faliang Zhang (中国科学与技术学报, 2025)
With the development of social economy, environmental problems have become prominent, and sustainable development has emerged as an important model. In the deep foundation pit projects of subway construction, steel supports are widely used. However, traditional corbel brackets have many disadvantages. This article is based on the Urumqi South Railway Station project and conducts an optimized design of the corbel bracket structure, adopting a square steel hanging plate, steel hooks, and a steel plate bottom bracket structure. Through research, the optimized design has significant advantages. It saves 174,000 yuan for the project, increases construction efficiency by 70%, and effectively reduces the risks of working at heights. It eliminates the welding process, is adjustable in position, and is convenient for construction. From the perspective of sustainable development, this design reduces steel consumption, can be reused, reduces resource input costs, reduces construction noise and dust pollution, realizes resource recycling, reduces maintenance costs, and enhances structural durability. It meets the requirements of economic, social, and environmental sustainable development and provides a useful reference for subway tunnel construction.